(untitled) (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Liver is an essential organ of our body that can be damaged by poisonous effects of chemicals, toxins, prolonged and uncontrolled use of drugs. Green tea is a popular beverage which may have hepatoprotective effect. Objective: To observe the effect of green tea (Camellia sinensis) on paracetamol induced liver damage in Long Evans male rats. Methods: This study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from July 2018 to June 2019. A total number of thirty (30) apparently healthy Long Evans male rats, 90-120 days old, weighing between 150-200g was taken for the study. After acclimatization for 14 days, they were divided into two groups, control group (Group A) and experimental group (Group B - green tea pretreated and paracetamol treated group). Control group was subdivided into group A1 (baseline control group) and group A2 (paracetamol treated control group). Each of this group was consisted of ten rats. All the rats received basal diet for 28 days. In addition to basal diet, baseline control group also received normal saline (20 ml/kg/day) orally daily for 28 days. Paracetamol treated control group received paracetamol orally (1.5 g/kg/day) for last 3 days (26th to 28th days) of the study period. Again experimental group received ethanolic extract of green tea orally (500 mg/kg/day) for 28 days and paracetamol orally (1.5g/kg/day) for last 3 days (26th to 28th days) of the study period. All the rats were sacrificed on 29th day. After sacrifice blood and liver sample was collected. Blood sample was collected from heart. Serum levels of total bilirubin, ALT and ALP were measured. One way ANOVA test, post hoc-Bonferroni test and Chi-square test were done to compare the data as applicable. Result: The mean serum total bilirubin, ALT and ALP levels were significantly higher in paracetamol treated control group and green tea pretreated and paracetamol treated group in comparison to those of baseline control group. Again, mean serum total bilirubin, ALT and ALP levels were significantly lower in green tea pretreated and paracetamol treated group than those of paracetamol treated control group. Conclusion: This study revealed that green tea has hepatoprotective effect against paracetamol induced liver damage in Long Evans male rats J. Dhaka National Med. Coll. Hos. 2022; 28 (02): 28-34